Inspiratory muscle warm-up and inspiratory muscle training: Separate and combined effects on intermittent running to exhaustion - Lomax, M.; Grant, I.; Corbett, J. (Journal of Sports Sciences, 2011)
In the present study, we examined the independent and combined effects of an inspiratory muscle warm-up and inspiratory muscle training on intermittent running to exhaustion. Twelve males were recruited to undertake four experimental trials. Two trials (Trials 1 and 2) preceded either a 4-week training period of 1 × 30 breaths twice daily at 50% (experimental group) or 15% (control group) maximal inspiratory mouth pressure (PImax). A further two trials (Trials 3 and 4) were performed after the 4 weeks. Trials 2 and 4 were preceded by a warm-up: 2 × 30 breaths at 40% PImax. Pre-training PImax and distance covered increased (P < 0.05) similarly between groups after the warm-up (11% and 5-7% PImax and distance covered, respectively). After training, PImax increased by 20 ± 6.1% (P < 0.01; d = 3.6) and 26.7 ± 6.3% (P < 0.01; d = 3.1) when training and warm-up were combined in the experimental group. Distance covered increased after training in the experimental group by 12 ± 4.9% (P < 0.01; d = 3.6) and 14.9 ± 4.5% (P < 0.01; d = 2.3) when training and warm-up interventions were combined. In conclusion, inspiratory muscle training and inspiratory muscle warm-up can both increase running distance independently, but the greatest increase is observed when they are combined.